Between Freedom of Enterprise and the Right to Work: Limits on the Post-Contractual Non-Compete Clause - Alemán-Madrigal, Luis Ernesto; Gutiérrez Palacios, Alexandra Marcela (Scientific journal of social studies, 2026)
This study analyzes the inclusion of post-employment non-compete clauses in employment contracts in Nicaragua. The absence of explicit regulation, systematic doctrinal development, and national jurisprudential criteria has led to their widespread use in contractual practice without a clear definition of their effects, creating risks of infringing upon fundamental rights, particularly the freedom of work and the free choice of profession or trade.From a dogmatic and comparative perspective, this study examines the tension between the protection of business interests—such as trade secrets and strategic information—and the constitutional freedoms of workers, identifying the proportionality criteria used in other legal systems to assess the validity of these clauses. The research, conducted using historical-logical, analytical-synthetic, and hypothetical-deductive methods, demonstrates that post-contractual non-compete agreements lack legal validity in the Nicaraguan context because they violate principles of labor law, highlighting the need to establish regulatory parameters that define their scope.
Keywords: Working Conditions; Freedom of Contract; Restrictive Clauses; Professional Autonomy; Transfer of Legal Models